2019
DOI: 10.1055/s-0039-1684048
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cisplatin-Induced Ototoxicity and Prevention

Abstract: Cisplatin is a highly effective antineoplastic agent used to treat solid tumors. Unfortunately, the administration of this drug leads to significant side effects, including ototoxicity, nephrotoxicity, and neurotoxicity. This review addresses the mechanisms of cisplatin-induced ototoxicity and various strategies tested to prevent this distressing adverse effect. The molecular pathways underlying cisplatin ototoxicity are still being investigated. Cisplatin enters targeted cells in the cochlea through the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 59 publications
5
94
1
3
Order By: Relevance
“…Historically, both ex vivo and in vivo studies have provided important insights into the mechanisms underlying hair cell death pathways (Wu et al, 2001; Wang et al, 2004; Rybak, 2007; Rybak et al, 2007; Guthrie, 2008; Warchol, 2010; Ding et al, 2011; Schacht et al, 2012; Francis et al, 2013; Nicholas et al, 2017). The conclusions, however, differ significantly between the ex vivo and in vivo context, and thus have created confusion in the ototoxicity field.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, both ex vivo and in vivo studies have provided important insights into the mechanisms underlying hair cell death pathways (Wu et al, 2001; Wang et al, 2004; Rybak, 2007; Rybak et al, 2007; Guthrie, 2008; Warchol, 2010; Ding et al, 2011; Schacht et al, 2012; Francis et al, 2013; Nicholas et al, 2017). The conclusions, however, differ significantly between the ex vivo and in vivo context, and thus have created confusion in the ototoxicity field.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is associated with increased oxidative stress and post-translational changes in the components of the apoptotic pathways [12,13]. Stress-activated protein kinases are critical components of this intracellular signaling network [20].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, ototoxicity is one of the most serious concerns because of the risk of permanent hearing loss associated with cochlear damage. The ototoxic mechanisms of cisplatin have gradually been identified, and oxidative stress has been implied as one of the main pathophysiologies [12,13]. In vitro experiments showed that cisplatin raises ROS levels and depletes the intracellular concentration of glutathione [14].…”
Section: Introductionmentioning
confidence: 99%
“…Insight into these ion homeostatic mechanisms may be important to understanding their functional contribution to hearing and hearing loss (Nickel & Forge, 2008;Zdebik, Wangemann, & Jentsch, 2009). These gene regulatory networks within the unperturbed wild type adult mouse SV establish a basis for identifying and interpreting changes in these networks in disease settings including, but not limited to, Meniere's disease (Collin et al, 2008;Ishiyama, Tokita, Lopez, Tang, & Ishiyama, 2007;Kariya et al, 2009), autoimmune inner ear disease (Calzada, Balaker, Ishiyama, Lopez, & Ishiyama, 2012), cisplatin-induced hearing loss (Breglio et al, 2017;Rybak, Mukherjea, & Ramkumar, 2019), and enlarged vestibular aqueduct syndrome (T. Ito, Nishio, Wangemann, & Griffith, 2015;Miyagawa et al, 2014).…”
Section: Implications For Understanding Ionic Homeostasis In the Innementioning
confidence: 99%